Style Analysis of Malaysian Islamic Bond Unit Trust Funds - Ahmad Harith Ashrofie, Hanafi (2014)
This study examines whether or not asset allocation styles of unit trusts different from their original objectives over the study period and sub-periods, which are during and after the financial crisis. The period of study is six (6) years starting from January 2007 to December 2012 and has been divided into overall period from January 2007 to December 2012 and two sub-periods: financial crisis from January 2007 to December 2009 and post financial crisis from January 2010 to December 2012. This study uses MSCI Malaysia Growth Index, MSCI Malaysia Value Index, 1-month Kuala Lumpur Inter-bank Offer Rate (KLIBOR), TRBPAM Islamic Government Index, TRBPAM Islamic Corporate Index, MSCI World Index as benchmarks for asset classes. The total of 14 Islamic bond funds used as sample and analysed using Return Based Style Analysis (RBSA). The results show there are some unit trusts that have significant different styles when compared to their original objectives for overall period and two sub-periods, either during financial crisis or post financial crisis period. The variation in monthly returns for most of the funds for overall period and sub- periods mainly could be explained by the variation in their styles. The average style of overall period and two sub- periods shows that fund managers have focused their investment mainly in bonds, either the government or corporate bonds. However, there is a small proportion of investment is placed in asset classes such as equity and money market instruments. The average fund returns could be explained mainly by the variation in the funds’ styles.